[Obras de Alvar Aalto en el período 1960-1982]
Se compilan obras del arquitecto Alvar Aalto comprendidas entre los años 1960-1982. Contiene: Parochial Church, Seinäjoki, 1958-60. Town Hall, Seinäjoki, 1963-65. Municipal Library, Seinäjoki, 1963-65. Folk Museum of Central Finland, Jyväskylä, 1959-62. Parochial Center, Wolfsburg, W. Germany, 1959-62. Parochial Center, Detmerode, W. Germany, 1965-68. Library, Rovaniemi, 1965-68. Akateeminem Bookshop, Helsinki, 1966-69. Art Museum, Aalborg, Denmark, 1969-73. Alvar Aalto Museum, Jyväskylä, 1971-73. Lappia House, Theater and Congress Hall, Rovaniemi, 1970-75. Finlandia Concert Hall and Congress Hall, Helsinki, 1967-75. Church, Lahti, 1970-78. Parochial Church, Riola, Italy, 1975-78. Town Theater, Jyväskylä, 1982.
Keywords: AALTO, ALVAR; FINLANDIA; SEINÄJOKI; JYVÄSKYLÄ; ALEMANIA; WOLFSBURG; ROVANIEMI; HELSINKI; DINAMARCA; AALBORG; ITALIA; BOLOGNA; ARQUITECTURA RELIGIOSA; EDIFICIOS RELIGIOSOS; IGLESIAS; MUNICIPALIDADES; BIBLIOTECAS; BIBLIOTECAS MUNICIPALES; MUSEOS; LOCALES COMERCIALES; TEATROS; MUSEOS DE ARTE; MUSEOS DE ARQUITECTURA; SALAS DE CONCIERTOS; DETMERODE; LAHTI